2014
DOI: 10.1371/journal.pone.0115109
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Inequality and Population Health in Low and Middle Income Countries: Policy Myth or Social Reality?

Abstract: An influential policy idea states that reducing inequality is beneficial for improving health in the low and middle income countries (LMICs). Our study provides an empirical test of this idea: we utilized data collected by the Demographic and Health Surveys between 2000 and 2011 in as much as 52 LMICs, and we examined the relationship between household wealth inequality and two health outcomes: anemia status (of the children and their mothers) and the women' experience of child mortality. Based on multi-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 42 publications
1
33
0
1
Order By: Relevance
“…The UN Inter-agency Group for Child Mortality Estimation (UN IGME) reported that, out of 99 surveyed LMICs, children born to the poorest families were on average, twice as likely to die before the age of five compared with children born to the wealthiest families [5]. Using data from 52 LMICs in the Demographic Health Surveys (DHSs) between 2000 and 2011, Van Deurzen et al found that more women experienced child mortality in countries with higher wealth inequality [9]. In another study which used DHS data (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) from LMICs, Bendavid showed that under-5 mortality was falling faster among the poorest families compared with the least poor [10].…”
Section: Introductionmentioning
confidence: 99%
“…The UN Inter-agency Group for Child Mortality Estimation (UN IGME) reported that, out of 99 surveyed LMICs, children born to the poorest families were on average, twice as likely to die before the age of five compared with children born to the wealthiest families [5]. Using data from 52 LMICs in the Demographic Health Surveys (DHSs) between 2000 and 2011, Van Deurzen et al found that more women experienced child mortality in countries with higher wealth inequality [9]. In another study which used DHS data (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) from LMICs, Bendavid showed that under-5 mortality was falling faster among the poorest families compared with the least poor [10].…”
Section: Introductionmentioning
confidence: 99%
“…The positioning of the municipalities in the different groups of the PAP, manifets their economic activity and inter-relations (GDP) as well as the number of their inhabitants. This being the case, a greater population relative to the generation of wealth, spreads itself and puts the large and richest municipalities in an inferior position in the groups 45 . Going beyond a certain level of the per capita GDP, the way of the distribution of wealth has become more important for explaining the health situation of the population 46 .…”
Section: Ratesmentioning
confidence: 99%
“…The relationship between poverty and child mortality has been known and recognized for many decades and has been the subject of several studies. [1][2][3] It can be seen that the causes of poverty are multiple, social, cultural, climatic, historical, anthropological, being the most important of all economic, translated by the concentration of income in the hands of few people scattered in some countries of the world. especially in North America, Europe, Japan and emerging countries such as Russia, India, China and Brazil.…”
mentioning
confidence: 99%